Population Dynamics of Tomato Leaf Miner, Tuta absoluta (Meyrick, 1917), in Various Locations of Surkhet, Nepal - Rokaya, Chitra Bahadur; Tiwari, Sundar; Thapa, Resham Bahadur; Pokhrel, Min Raj (Journal of Agriculture and Forestry University, 2025)
The tomato leaf miner, Tuta absoluta (Meyrick, 1917), is a destructive pest of tomatoes and other solanaceous plants, inflicting severe yield losses globally. A population dynamics study of T. absoluta in tomato provides an opportunity to understand interactions among biotic and abiotic factors, which are useful to develop a pest management strategy. The population dynamics was observed for a year from May 2024 to May 2025 at nine sites of Surkhet spread across 598 to 724 masl. The study focused on five popular tomato varieties and two growing conditions (plastic house and open-field). Male adult populations was found to have declined by 33.33% over an elevation increase of 126 m, with infestation intensity inversely correlated (r = -0.45). Adult population peaked at temperatures between 25-35 °C (r = +0.71, p < 0.0001), whereas rain greater than 10 mm suppressed population growth by physically washing off eggs and larvae from host plants, increasing mortality through direct impact, and contributing to environmental conditions less favorable for population proliferation. Tomato variety VL 443 exhibited the tolerance (only 41% infestation) while Heemsohna showed the preference (100% infestation) variety. Furthermore, plastic house tomato had a significant reduction in male adult leaf miner by 49% compared to open field growing conditions.